Enhancing Thermoelectric Performance of Mg3Sb2 Through Substitutional Doping: Sustainable Energy Solutions via First-Principles Calculations - Muhammad Owais; Xian Luo; Bin Huang; Yanqing Yang; Mudassar Rehman; Ray Tahir Mushtaq (Energies)
Mg3Sb2-based materials, part of the Zintl compound family, are known for their low thermal conductivity but face challenges in thermoelectric applications due to their low energy conversion efficiency. This study addressed these limitations through first-principles calculations using the CASTEP module in Materials Studio 8.0, aiming to enhance the thermoelectric performance of Mg3Sb2 via strategic doping. Density functional theory (DFT) calculations were performed to analyze electronic properties, including band structure and density of states (D.O.S.), providing insights into the influence of various dopants. The semiclassical Boltzmann transport theory, implemented in BoltzTrap (version 1.2.5), was used to evaluate key thermoelectric properties such as the Seebeck coefficient, electrical conductivity, electronic thermal conductivity, and electronic figure of merit (eZT). The results indicate that doping significantly improved the thermoelectric properties of Mg3Sb2, facilitating a transition from p-type to n-type behavior. Bi doping reduced the band gap from 0.401 eV to 0.144 eV, increasing carrier concentration and mobility, resulting in an electrical conductivity of 1.66 × 106 S/m and an eZT of 0.757. Ge doping increased the Seebeck coefficient to −392.1 μV/K at 300 K and reduced the band gap to 0.09 eV, achieving an electronic ZT of 0.859 with low thermal conductivity (11 W/mK). Si doping enhanced stability and achieved an electrical conductivity of 1.627 × 106 S/m with an electronic thermal conductivity of 11.3 W/mK, improving thermoelectric performance. These findings established the potential of doped Mg3Sb2 as a highly efficient thermoelectric material, paving the way for future research and applications in sustainable energy solutions.